MEDB-04. Young children with metastatic medulloblastoma: frequent requirement for radiotherapy in children with non-WNT/non-SHH medulloblastoma despite highly intensified chemotherapy – Results of the MET-HIT2000-BIS4 trial. (3rd June 2022) - Mynarek, Martin; Goschzik, Tobias; Kool, Marcel; von Hoff, Katja; Ottensmeier, Holger; Warmuth-Metz, Monika; Bison, Brigitte; Sill, Martin; Rushing, Elisabeth Jane; Hasselblatt, Martin; Koch, Arend; Schüller, Ulrich; et al.
Abstract: PURPOSE: To assess outcomes and biological parameters of children younger than 4 years with metastatic medulloblastoma treated within the MET-HIT2000-BIS4 trial or outside the protocol. PATIENTS AND METHODS: 48 trial participants received either carboplatin/etoposide (years 2001 to 2005, n=18) or an intensified Head-Start-based induction (years 2006 to 2011, n=30), both groups with intraventricular methotrexate, followed by high-dose chemotherapy (HDCT) and/or craniospinal radiotherapy (CSI). In an extended cohort, data of 58 additional were grouped with trial participant data. RESULTS: Trial participants (n=48): After intensified induction, both response (26/27 vs. 10/17 eligible patients, p=0.003), and progression-free survival (PFS, 5-year-PFS (5y-PFS): 57% vs 28%, p=0.014) was higher after intensified induction. However, CSI- /progression-free survival (CSIfPFS) was low (5-year CSIfPFS 17%). Biological subtype influenced 5y-CSIfPFS with 3% in non-WNT/non-SHH medulloblastoma vs. 58% in SHH-medulloblastoma (p<0.001), independent of induction regimens. Extended cohort (n=48 on trial and n=58 off trial): Non-WNT/non-SHH medulloblastoma (n=74, all treated in analogy to the MET-HIT2000-BIS4 protocol): Most frequent subtypes were II (5y-PFS 0%, 5y-OS 7%, n=21) and IV (5y-PFS 55%, 5y-OS 57%, n=16). 5y-CSIfPFS was only 8% [n=5]. Among patients in CR (n=13) or PR (n=10), who received HDCT but not CSI in primary therapy, only 5 were CSI-free survivors (CR: n=4/PR: n=1; Subtype III: n=1, Subtype IV: n=2, non-WNT/non-SHH by histology: n=2). SHH-medulloblastoma (n=32, treated with MET-HIT2000-BIS4 [n=16] or HIT2000-BIS4/HIT-SKK chemotherapy [with intrventricular methotrexate, without HDCT; n=16]): 5y-PFS (72%) and 5y-CSIfPFS (69%) did not differ according to therapy or SHH-subgroups. Two therapy-related deaths occurred on MET-HIT2000-BIS4 therapy. Relapses were more frequent after HIT-SKK (p=0.083). CONCLUSIONS: Despite maximally intensified chemotherapy, patients with metastatic non-WNT/non-SHH medulloblastoma almost always require craniospinal radiotherapy to survive their disease. In SHH-activated medulloblastoma, HDCT might better control the disease but careful vigilance of toxicity is important.